Fluid power: a textbook of hydraulics and pneumatics - K, Chandrashekara P (Everest Publishing House, 2010)
Fluid power: a textbook of hydraulics and pneumatics / K, Chandrashekara P. -- Pune: Everest Publishing House, 2010 620.106 K11e13 13th rev ed No. of Copies : 1